2017
DOI: 10.1021/acssynbio.7b00105
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterization of DNA Strand-Displacement Circuits in Serum-Supplemented Cell Medium

Abstract: The functional stability and lifetimes of synthetic molecular circuits in biological environments are important for long-term, stable sensors or controllers of cell or tissue behavior. DNA-based molecular circuits, in particular DNA strand-displacement circuits, provide simple and effective biocompatible control mechanisms and sensors, but are vulnerable to digestion by nucleases present in living tissues and serum-supplemented cell culture. The stability of double-stranded and single-stranded DNA circuit comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 38 publications
0
41
0
Order By: Relevance
“…One of the long-standing goals of DNA nanotechnology is to create autonomous molecular machines that can operate in harsh biological environments and provide drug-delivery or diagnostic functionality46. Recent studies have shown that the functionality of simple DSD circuits is severely limited in cell culture medium with 10% foetal bovine serum (FBS) 47. We performed a series of experiments to investigate whether proteinosomes could be used to protect DSD networks from degradation in a biological environment.…”
Section: Operation Of Dna Circuits In a Biologically Relevant Environmentioning
confidence: 99%
“…One of the long-standing goals of DNA nanotechnology is to create autonomous molecular machines that can operate in harsh biological environments and provide drug-delivery or diagnostic functionality46. Recent studies have shown that the functionality of simple DSD circuits is severely limited in cell culture medium with 10% foetal bovine serum (FBS) 47. We performed a series of experiments to investigate whether proteinosomes could be used to protect DSD networks from degradation in a biological environment.…”
Section: Operation Of Dna Circuits In a Biologically Relevant Environmentioning
confidence: 99%
“…They also were tested against a more aggressive exonuclease, snake‐venom phosphodiesterase, where surprisingly the DPAs showed resistance similar to that of Exo III. In a different vein of native structural modification, Fern and Schulman recently studied the effect of different secondary structures on DNA circuit strands . In Dulbecco's modified Eagle medium media supplemented with 10% FBS and competing ssDNA, a 3′ hairpin domain in the DNA circuit increases lifetime and functionality over a 7 h incubation.…”
Section: Dna Nanostructure Stability and Biocompatibilitymentioning
confidence: 99%
“…Supplementing media with MgSO 4 reduces denaturation by low cation availability, and addition of inhibitory agents allows the DNA nanostructures to stealthily evade degradation by nucleases. Supplementing with actin or ssDNA (such as poly‐T or salmon sperm DNA) efficiently out compete the more important DNA nanostructure components for nuclease activity. Heat treatment of serum is an effective method of reducing nuclease activity, but it does not support viable cell culturing .…”
Section: Dna Nanostructure Stability and Biocompatibilitymentioning
confidence: 99%
“…One of the long-standing goals of DNA nanotechnology is to create autonomous molecular machines that can operate in harsh biological environments and provide drug-delivery or diagnostic functionality 45 . Recent studies have shown that the functionality of simple DSD circuits is severely limited in cell culture medium with 10% fetal bovine serum (FBS) 46 . We performed a series of experiments to investigate whether proteinosomes could be used to protect DSD networks from degradation in a biological environment.…”
Section: Operation Of Dna Circuits In a Biologically Relevant Environmentioning
confidence: 99%